Preferences on Redistribution in Fragmented Labor Markets in Latin America and the Caribbean - Sarah Berens (Journal of Politics in Latin America, 2015)
This study investigates the extent to which labor market dualization polarizes preferences on redistribution between formal and informal sector workers in Latin America and the Caribbean. Differences in welfare state costs and benefits for these labor market groups are likely to fuel diverging incentives regarding welfare consumption. The article tests whether or not informal workers are driven mainly by economic self-interest to increase gains from public welfare goods. The study employed a hierarchical model on pooled survey data from the Latin American Public Opinion Project (LAPOP) 2008 and 2010 to analyze the risk exposure of formal and informal workers and, subsequently, their preferences on redistribution. The analysis reveals that while economic self-interest is an influential factor for formal workers, it is (unexpectedly) much less so for informal workers. Also, an increased economically insecure environment, reflected by high unemployment rates, does not motivate informal workers to an exceptional degree to turn towards the state for redistribution, despite greater exposure to economic risk. Labor market dualization does not translate into polarization at the individual level regarding redistributive preferences in Latin America and the Caribbean.